Effect of taro tubers silage (Colocasia esculenta (L.) Schott) on the morphometry of the gastrointestinal tract of growing pigs - Caicedo, W.; Rodríguez, R.; Lezcano, P.; Vargas, J. C.; Uvidia, H.; Valle, S.; Flores, L. (Cuban Journal of Agricultural Science, 2017)
In order to know the effect of taro tubers silage on the morphometric and morphological indicators of the gastrointestinal tract (GIT) of growing pigs, a total of 24 pigs from the Landrace x Duroc x Pietrain commercial crossbreeding with an initial mean live weight of 25.65 ± 0.56 kg were used. The pigs were distributed according to a random block design in four treatments: T1 control diet (maize and soybean); T2, T3 and T4 (substitution in the diet of 33, 66 and 100 % of maize by taro silage of 8 d of production with whey and molasses B of sugarcane) with an equal number of animals per treatment. The results were processed by analysis of variance. The means were contrasted with the Duncan test (P <0.05). The lowest weight (P <0.05) of the GIT, large intestine, pancreas and higher weight of the stomach; caecum and liver were presented by the pigs that intake silage. The higher length of the GIT, small intestine andcaecum was recorded in treatments T2, T3 and T4, respectively. It is suggested that it is feasible to use taro tubers silage in substitution ofmaize fbecause there was no negative influence on the morphometry of the gastrointestinal organs of growing pigs. Key words: alternatives food, fermentation, digestive tract,pigs.